Loan Default Prediction Using Artificial Neural Networks - Suyash Srivastava, G. Saranya, Anmol Pratap, Rohit Agrawal, Anubhav Jain (International Journal of Advanced Science and Technology, 2020)
Lending loans can be an arduous affair for banks and their management, and so it becomes very important to automate the process of loan lending. Thus it is very much necessary to predict whether a loan will be returned or not. We proposed a prediction model that will perform loan default prediction using the Artificial Neural Networks (ANN) technique of Machine Learning and compare it with the Logistic Regression technique. We trained our model on a pre-recorded dataset to predict whether or not the borrower would default and we aimed to achieve best possible results.Keywords: Loan Default, ANN, Logistic Regression.